[Black speaker at University Union plaza podium] (1995)
The speaker, dressed in a black suit and tie, is flanked by two other Black people also in suits and ties. In the foreground, there are two White people below the stage level pointing a video camera at the speaker. There are several people seated on the stage behind the speaker.